2022
DOI: 10.3390/jcm11164763
|View full text |Cite
|
Sign up to set email alerts
|

Management of Preschool Wheezing: Guideline from the Emilia-Romagna Asthma (ERA) Study Group

Abstract: Preschool wheezing should be considered an umbrella term for distinctive diseases with different observable and measurable phenotypes. Despite many efforts, there is a large gap in knowledge regarding management of preschool wheezing. In order to fill this lack of knowledge, the aim of these guidelines was to define management of wheezing disorders in preschool children (aged up to 5 years). A multidisciplinary panel of experts of the Emilia-Romagna Region, Italy, addressed twelve different key questions regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 114 publications
(256 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, RSV is the most frequent cause of lower RTI, mainly bronchiolitis, in infants [ 19 ]. Several epidemiological studies demonstrated that a history of severe RSV bronchiolitis is associated with subsequent persistent wheezing, childhood asthma or both [ 10 , 26 ]. RSV infection causes necrosis of the bronchiolar epithelium with subsequent submucosal oedema, recruitment of polymorphonuclear leukocytes and massive release of pro-inflammatory mediators, increased mucus secretion and bronchoconstriction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, RSV is the most frequent cause of lower RTI, mainly bronchiolitis, in infants [ 19 ]. Several epidemiological studies demonstrated that a history of severe RSV bronchiolitis is associated with subsequent persistent wheezing, childhood asthma or both [ 10 , 26 ]. RSV infection causes necrosis of the bronchiolar epithelium with subsequent submucosal oedema, recruitment of polymorphonuclear leukocytes and massive release of pro-inflammatory mediators, increased mucus secretion and bronchoconstriction.…”
Section: Resultsmentioning
confidence: 99%
“…We set up a multidisciplinary panel of experts that included all the Heads of the Paediatric Units of Emilia-Romagna Region, Italy, the Heads of the outpatient clinics for pulmonology and allergology, a sample of primary care paediatricians (identified in each province based on the number of the paediatric population according to ISTAT 2018 data) and a patients’ association (Respiro Libero, Parma, Italy). This study group (named Emilia-Romagna Asthma Study Group and described in detail in a previous publication on the management of children with acute asthma attacks [ 8 ] included members with previous experience in the development of documents and recommendations with the Grading of Recommendations Assessment, Development, and Evaluation [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wheezing is an “umbrella” term, including heterogeneous clinical conditions with different respiratory phenotypes. It has been estimated that approximately 50% of children experience at least one wheezing episode before age 6 years [ 18 ].…”
Section: Short-acting Bronchodilators: Indications In Pediatric Respi...mentioning
confidence: 99%
“…Asthma is the most common chronic disease of childhood in the world, and asthma exacerbation is frequently caused by viral infections [ 11 , 12 ]. Initially, asthma patients were classified as an at-risk group for COVID-19 severe forms, but whether asthma has worse COVID-19 consequences is not yet clear [ 13 ].…”
Section: Incidence Of Sars-cov-2 Infection and Severity Of Disease In...mentioning
confidence: 99%